Dilemmas the Tarner lectures 1953 - Ryle, Gilbert 1900-1976 (Cambridge University Press, 2015)
Common sense tells me I can control my life to some extent; should I then, faced with a logical argument for fatalism, reject common sense? There seems to be no place in a physical theory of the universe for the sensory experiences of colours, taste and smells, yet I know I have these experiences. In this book, Gilbert Ryle explores the conflicts that arise in everyday life and shows that the either/or which such dilemmas seem to suggest is a false dilemma: one side of the dilemma does not deny what we know to be true on the other side. This classic book has been revived in a new series livery for twenty-first-century readers, featuring a specially commissioned preface written by Barry Stroud
Keywords: Dilemma; Philosophie; Logik; Begriff; Sprachphilosophie